Guidelines for Building Therapeutic Relationship for Nursing Students - ไวท์วิทย์ริยะกุล นิภาธร; ลาภา ระพีพรรณ (Journal of Ratchathani Innovative Health Sciences, 2019)
Psychiatric nursing is a therapeutic skill considered to be an important aspect of nursing care. Nursing students who train in psychiatric clinics lack the skills and experience to build therapeutic relationships with psychiatric patients. For students, it is difficult to use them as a tool for psychiatric nursing. This article is intended to be utilized as a guideline for the development of therapeutic relationships for nursing students. Nursing students must have knowledge and understanding of the relational elements for treatment in the conversation process of healing. This article presents a framework for building therapeutic relationship between nursing students and patients and encourages nursing students to learn to become more effective role models. The teaching model, feedback information, social reinforcement and suggested training and practice for nursing students is demonstrated using simulated situations. This is a guideline for building relationships between nursing students and psychiatric patients. This guideline will be beneficial in teaching nursing students about general mental health and psychiatric nursing in order to provide a more efficient and beneficial result.